All-male hybrids of a tetrapod Pelophylax esculentus share its origin and genetics of maintenance - Doležálková-Kaštánková, Marie; Pruvost, Nicolas B M; Plötner, Jörg; Reyer, Heinz-Ulrich; Janko, Karel; Choleva, Lukáš (Biology of sex differences, 2018)
BACKGROUND: Sexual parasites offer unique insights into the reproduction of unisexual and sexual populations. Because unisexuality is almost exclusively linked to the female sex, most studies addressed host-parasite dynamics in populations where sperm-dependent females dominate. Pelophylax water frogs from Central Europe include hybrids of both sexes, collectively named P. esculentus. They live syntopically with their parental species P. lessonae and/or P. ridibundus. Some hybrid lineages consist of all males providing a chance to understand the origin and perpetuation of a host-parasite (egg-dependent) system compared to sperm-dependent parthenogenesis. METHODS: We focused on P. ridibundus-P. esculentus populations where P. ridibundus of both sexes lives together with only diploid P. esculentus males. Based on 17 microsatellite markers and six allozyme loci, we analyzed (i) the variability of individual genomes, (ii) the reproductive mode(s) of all-male hybrids, and (iii) the genealogical relationships between the hybrid and parental genomes. RESULTS: Our microsatellite data revealed that P. esculentus males bear Mendelian-inherited ridibundus genomes while the lessonae genome represents a single clone. Our data indicate that this clone did not recently originate from adjacent P. lessonae populations, suggesting an older in situ or ex situ origin. CONCLUSIONS: Our results confirm that also males can perpetuate over many generations as the unisexual lineage and successfully compete with P. ridibundus males for eggs provided by P. ridibundus females. Natural persistence of such sex-specific hybrid populations allows to studying the similarities and differences between male and female reproductive parasitism in many biological settings.
Keywords: hybridizace genetická; Genotype; zvířata; Hybridization, Genetic; Sexual parasites; mikrosatelitní repetice; mužské pohlaví; Reptilian Proteins; Unisexual; Microsatellite Repeats; proteiny plazů; Water frog; Hemiclone; Ranidae; Animals; Hybridogenesis; genotyp; All-male lineage; Pelophylax; Male